2016
DOI: 10.1590/abd1806-4841.20165066
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the histopathology of chronic urticaria and its clinical picture

Abstract: BACKGROUNDChronic urticaria is characterized by transient, pruritic lesions of varying sizes, with central pallor and well-defined edges, with disease duration longer than six weeks. Its cellular infiltrate consists of neutrophils, lymphocytes and eosinophils. There is a subgroup of patients with eosinophilic or neutrophilic urticaria, resistant to the treatment with antihistamines, but that respond to a combination of antihistamine with other drugs.OBJECTIVETo evaluate the present infiltration in chronic urti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
1
11
0
2
Order By: Relevance
“…Eosinophils were observed in the majority of CSU cases, particularly in those with bruising, which is in agreement with several studies that have shown an association between eosinophilic inflammatory infiltrates and more exuberant clinical pictures of CSU 11,19‐21 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Eosinophils were observed in the majority of CSU cases, particularly in those with bruising, which is in agreement with several studies that have shown an association between eosinophilic inflammatory infiltrates and more exuberant clinical pictures of CSU 11,19‐21 …”
Section: Discussionsupporting
confidence: 91%
“…Our study included 45 patients with a clinical diagnosis of CSU resistant to high doses of H1‐antihistamines with a higher percentage of females, in accordance with the demographic profile of the disease, 11,12 and many cases with a long duration of urticaria, as our department is a UCARE referral center for CU. Several patients exhibited occasional lesions that lasted longer than 24 hours and progressed to a violaceous hue (bruising) before complete fading, but none of these patients had systemic symptoms, low complement levels, or prominent vasculitis on histopathology.…”
Section: Discussionmentioning
confidence: 99%
“…14 In a study conducted by our group in 2016, we demonstrated that urticaria with predominance of eosinophils was related to greater clinical activity of the disease. 15 Other authors have described the presence of CD4 + T lymphocytes, variable number of monocytes, basophils, and lymphocytes. 2,16 The cytokines involved in the inflammatory skin process in urticaria reveal a mixed cytokine pattern with an increase in IL-4, IL-5, and IFN gamma.…”
Section: Discussionmentioning
confidence: 98%
“…Eosinophils also participate in chronic urticaria, primarily in patients lacking an autoimmune component, and accumulate in urticarial lesions where MBP and ECP can also be detected . Marques et al recently conducted a study where they found that tissue eosinophilia was linked to disease severity in patients with chronic urticaria.…”
Section: Mast Cells and Eosinophils In Allergic Diseasementioning
confidence: 99%